Synthesis and Characterization of Copper Ferrite Nanoparticles for Efficient Photocatalytic Degradation of Organic Dyes - Julia Mazurenko; A. K. Sijo; Larysa Kaykan; Volodymyr Kotsyubynsky; Łukasz Gondek; Antoni Zywczak; Mateusz Marzec; Oleksii Vyshnevskyi (Journal of Nanotechnology)
This paper reports the successful synthesis of spinel-type CuFe2O4 ferrite nanoparticles with an average particle size of 24 nm, produced using the citrate sol–gel autocombustion method. The structure of the synthesized material was analyzed through x-ray diffraction (XRD) and further supported by Raman and FT-IR spectroscopy. The analysis confirmed that the material formed a spinel ferrite structure with the Fd3m space group. Valence states and energy levels of the elements were examined using x-ray photoelectron spectroscopy (XPS). Surface morphology was studied using scanning electron microscopy (SEM), coupled with elemental analysis. The magnetic properties of the synthesized CuFe2O4 ferrite nanoparticles were investigated using a vibrating sample magnetometer (VSM). Magnetization measurements revealed that the sample exhibited characteristic magnetic parameters of copper ferrite, with a saturation magnetization (Ms) of 23.10 emu/g, a coercivity Hc of 415 Oe, and a remnant magnetization (Mr) of 12.80 emu/g. These magnetic properties enable efficient magnetic separation of the nanoparticles from aqueous solutions, thereby enhancing process efficiency and minimizing catalyst loss during photocatalytic applications. Optical and photocatalytic properties were investigated using spectrophotometry, revealing an optical band gap of 1.85 eV, which demonstrates potential for photocatalytic activity under visible light. The CuFe2O4 ferrite effectively degraded dyes such as methylene blue (MB), malachite green (MG), Safranine (S), Congo Red (CR), and Rhodamine B (RhB) within 180 min, highlighting its practical application potential. The study identified that hydroxyl radicals (·OH), generated from H2O2 decomposition under visible light irradiation, played a critical role in enhancing the efficiency of the photo-Fenton reaction. A proposed mechanism involves the excitation of CuFe2O4 under visible light, facilitating electron transfer that leads to the generation of ·OH radicals, which degrade the dye molecules. Among the tested dyes, CR exhibited the highest degradation percentage with a rate constant of 0.033 min⁻1 and followed a pseudo-first-order kinetic model. The effect of hydrogen peroxide concentration on dye degradation efficiency was also evaluated.